ANALISIS SEMIOTIK IKLAN KOSMETIK POND’S PADA STASIUN TELEVISI RCTI DALAM MEMBENTUK CITRA PEREMPUAN - La Tarifu (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2017)
This study aims to describe connotative and denotative meaning in the product of Pond’s White Beauty as a form of woman imagery. The object of this research is the product advertisement of Pond's White Beauty on every duration of the Dahsyat television show which aired on RCTI which has a duration of three and a half hours running by observing scene on Pond’s White Beauty advertisement. The theory used in this research is Roland Barthes semiotic theory. The data obtained from this research are analyzed by using Qualitative Descriptive Technique. The results of this study show that the connotative meaning of Pond's White Beauty advertisement in defining the beauty as if you have white skin, white and smooth face, while the denotative meaning in Pond’s White Beauty advertisement is Pond’s White Beauty products can nourish the skin from the inside which make the skin looks whiter and shine if it is used every day. Keywords: semiotics, advertising, cosmetics, Pond's, imagery, women